Le château de Gréoux-les-Bains (Alpes-de-Haute-Provence) Une résidence seigneuriale du Moyen Âge à l'Époque moderne - Claude, Sandrine (Documents d'archéologie française, 2000)
The Château de Gréoux-les-Bains was built in the heart of Provence on a site which had been used from early Roman times for its hot springs. The castle's powerful outline dominates the village whose organisation and architecture has preserved evidence of its development from the Middle Ages to the modern period. In the present work, Sandrine Claude combines analysis of archival sources, selected excavation data and standing remains - making particular use of building archeology - to determine the origins and ambitions that presided over the building of a castle whose size is disproportionate to its geographical and human context. The castle's little known history and its architectural development are thus retraced and the monument placed in its human environment, that of its commissioners and successive owners.